The latest approaches to teaching a business foreign language according to professional orientation: information technologies (Pedagogy of Higher and Secondary Education, 2016)
Shalatska G. M. The latest approaches to teaching a business foreign language according to professional orientation: information technologies.The article consideres technique of teaching business foreign language according to professional orientation of students of the «Information Technology» specialty. Research objective is to consider the possibility of an intensification studying of business English for the professional direction using different types of tasks and digital information-communication technologies in the educational process during the training of future experts in the field of information technologies. Examples of exercises and tasks in order to develop lexical material, situations of business communication are given.The main stages of work for development of the material needed for studying of business English on a professional orientation is outlined. Business game helps to simulate situations in the business world. The purpose of the educational game situations is to prepare students of «Information Technology» specialty for effective communication in a foreign language in the professional sphere. The use of authentic texts from the actual directions of development of modern information technologies is recommended. On the basis of these texts it is offered to hold press conferences with application of design technologies and an interactive board. Students have to develop the ability to make the summary, the business card, to process official documents, to conduct conversation by phone, to conduct conversation with employees and colleagues. Ways of broaden students’ outlook and motivation of their independent work are specified. For, example, using of educational platforms, such as FutureLearn, will promote students motivation and deepening their knowledge.Prospects of further researches on this problem are defined. It is necessary to define typical situations of business communication in the sphere of students professional activity and to formulate practical skills of understanding business language. Development of textbooks and arrange of bilingual terminological dictionaries of Business English for professional direction will contribute to the development of professional qualities of the future programmers. Business language will become an important step in the formation process of professionalism and increase the competitiveness level of experts in the labor market.
Keywords: information technologies; tendency; field of knowledge; Internet; professional sphere; intensification; motivation; educational platform